Training and Working Environment on Science Teachers’ Performance - Humiras Betty Marlina Sihombing; Sherly; Edy Dharma; Desmalia Purba; Kisno (Jurnal Penelitian Pendidikan IPA, 2023)
The objective of this study was to gain a deeper understanding of the training, working conditions, and performance of sains teachers at Sultan Agung Pematang Siantar Private High School, as well as to explore the impact of these factors on teacher performance. The study utilized both field research and a review of existing literature. The sample for the study consisted of thirty-seven (37) teachers from Sultan Agung Pematang Siantar Private School. The study's data comprised quantitative and qualitative information from primary and secondary sources. Data collection was carried out through surveys, interviews, and examination of relevant documents. Various analytical methods including qualitative descriptive analysis, quantitative descriptive analysis, and normality tests were employed to analyze the data. The findings of the study revealed that teacher performance at Sultan Agung Pematang Siantar Private Elementary and High School was rated as high, indicating that training and working conditions played a significant and positive role in the success of science teachers.